Therapeutic targets for neuroblastomas - Garrett M. Brodeur; Radhika Iyer; Jamie L. Croucher; Tiangang Zhuang; Mayumi Higashi; Venkatadri Kolla (2014)
Introduction: Neuroblastoma (NB) is the most common and deadly solid tumor in children. Despite recent improvements, the long-term outlook for high-risk NB is still < 50%. Further, there is considerable short- and long-term toxicity. More effective, less toxic therapy is needed, and the development of targeted therapies offers great promise.